PENGARUH AKTIVA PRODUKTIF, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS BANK UMUM KONVENSIONAL TBK - Arifah Nur Fadhilah, - (2019)
This study aims to determine the effect of Earning Assets, Liquidity and Firm Size on Profitability Bank. The population Population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) 2015-2017. The sampling technique used was purposive sampling and obtained a sample of 30 companies. The data analysis technique used is descriptive analysis using Microsoft Excel 2010 and the hypothesis in this study uses Panel Data Regression Analysis with the E-views version 9.0 program and a 5% significance level. The results of this study indicate that (1) Earning Assets (NPL) has negative influence on Profitability (ROA), (2) Liquidity (LDR) has positive influence on profitability (ROA), (3) firm size (SIZE) has positive influence on Profitability (ROA).